Analysis and Criticism of Narrations Regarding Prophet Joseph's So-called Attempted Adultery - Yalçın, Selami (Fırat University, 2022)
There are some interpretations in some tafsir books that Prophet Joseph tried to commit adultery with Aziz's wife. Giving different meanings to the word “????” “hemm” in the 24th verse of the chapter of Joseph, “???? ????????” in the 52nd verse, “I did not betray him.” The explanation of the expression by associating it with him has led to some discussions about the innocence of the prophets. For this reason, the full meaning of the word "hemm" and "I did not betray him" in the 52nd verse. It is important to reveal the identity of the person using the expression. In this research, firstly, the meaning of the word "hemm" was emphasized, and the explanations of the lexicographers about the meaning of the word were given. The verses and hadiths in which the word is used were examined. In this research, it has been understood that associating the 24th, 52nd and 53rd verses with each other is caused by a narration from Ibn Abbas and some interpretations of some tabiîn commentators, and that these narrations are valid. It has been concluded that these narrations and claims, which do not comply with the language structure of Arabic, incompatible with other verses and hadiths, and conflicts with the innocence of the prophets, are not mentioned in the Torah, but are likely to originate from Israeli sources.

Bazı tefsir kitaplarında Hz. Yûsuf’un, Aziz’in karısıyla zinaya teşebbüs ettiğine dair bazı yorumlara rastlanmaktadır. Yûsuf sûresi 24. âyette geçen “????” “hemm” kelimesine farklı anlamların verilmesi, 52. âyette geçen “???? ????????” “Ona ihanet etmedim.” ifadesinin de onunla ilişkilendirilerek açıklanması peygamberlerin masumiyetiyle ilgili bazı tartışmalara yol açmıştır. Bu nedenle “hemm” kelimesinin tam manasını ve 52. âyette geçen “Ona ihanet etmedim.” ifadesini kullanan kişinin kimliğini ortaya çıkartmak önem arz etmiştir. Bu araştırmada öncelikle “hemm” kelimesinin anlamı üzerinde durulmuş, lügat âlimlerinin kelimenin manasıyla ilgili açıklamaları aktarılmıştır. Kelimenin geçtiği âyetler ile hadisler incelenerek analiz edilmiştir. Yapılan araştırmada 24. âyet ile 52 ve 53. âyetleri birbirleriyle ilişkilendirmenin İbn Abbâs’tan (r.a.) gelen bir rivâyet ile bazı tabiîn müfessirlerinin bir takım yorumlarının sebep olduğu ve bu rivâyetlerin senedinin sahih olduğu anlaşılmıştır. Arapçanın dil yapısıyla, başka âyet ve hadislerle uyumlu olmayan ve peygamberlerin masumiyetiyle örtüşmeyen bu rivâyet ve iddiaların Tevrât’ta geçmediği ancak İsrâiliyyât kaynaklı olma ihtimalinin yüksek olduğu kanaatine varılmıştır. Âyetler ışığında olaylar ve Züleyha’nın karakter yapısı tahlil edilmiştir. Sûrenin simetrik yapısından 52-53. âyetlerde konuşan kişinin Züleyha olduğuna kanaat getirilmiştir.
Hz. Yûsuf’un Züleyha ile Zinaya Teşebbüs Ettiği İddiasıyla İlgili Rivâyetlerin Tenkidi
Keywords: Religious Studies; Din Araştırmaları